Desenvolvimento inicial e densidade de estocagem de larvas de Aracu-riscado, Leporinus agassizii (Characiformes: Anostomidae) - Ferreira, Luana Malheiros [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Studies for the production of young fish shapes are key to the development of fish farming and the management of natural populations. Leporinus agassizii is appreciated in the different fishing methods (commercial, craft, ornamental and sports), and present desirable features for creation. This study aimed to describe the embryonic and larval stocking density of aracu-riscado, L. agassizii. Players underwent reproduction induced hypophysation, with the water temperature at 28.6±0.7 °C, the Centro de Capacitação e Produção de Alevinos belonging to the Instituto Federal de Educação, Ciência e Tecnologia, São Gabriel da Cachoeira, Amazonas, Brazil, in September 2014. After fertilization, the eggs were kept in incubators (60 Litre), with the average water temperature of 28.4±0.7 °C. Samples were collected 10 min intervals on eggs during the first three hours after fertilization (AF) and thereafter at intervals of 30 minutes until the outbreak of the larvae, for observation in stereo equipped with digital color CMOS camera, 10.0 MP and software to capture and analyze images (ISCapture). The effect of larval stocking density of L. agassizii was assessed over 4th and 14th days after hatching (DAH). 3600 larvae were used in the 4th DAH, meeting these with the yolk sac fully absorbed, mouth open and fasted. The effect of larval stocking density of L. agassizii was assessed over 4th and 14th (DAH). 3600 larvae were used in the 4th DAH, meeting these with the yolk sac fully absorbed, mouth open and fasted. The larvae were subjected to density of 5 (D5), 15 (D15) and 25 (D25) larvas.L-1, in polyethylene boxes (0.63 x 0.45 x 0.32 m) with 20 Litre of water. We used a completely randomized design with four replications. The larvae were fed six times a day, each meal consisting of Artemia in the proportion 50 náuplios.larva-1 (4th to 6th DAH), 100 (7th to 9th DAH), 200 (10th to 11th DAH) and 400 (12th to 13th DAH) and commercial diet ...

Estudos para produção de formas jovens de peixes são fundamentais para o desenvolvimento da piscicultura e o manejo das populações naturais. Leporinus agassizii é apreciado nas distintas modalidades de pesca (comercial, artesanal, ornamental e esportiva), além de apresentar características desejáveis para a criação. Objetivou-se descrever o desenvolvimento embrionário e a densidade de estocagem de larvas do aracu-riscado, L. agassizii. Reprodutores foram submetidos a reprodução induzida por hipofisação, com a temperatura da água a 28,6 ± 0,7ºC, no Centro de Capacitação e Produção de Alevinos, pertencente ao Instituto Federal de Educação Ciência e Tecnologia, São Gabriel da Cachoeira, Amazonas, Brasil, no mês de setembro de 2014. Logo após a fertilização, os ovos foram mantidos em incubadoras (60L), com a temperatura média da água de 28,4 ± 0,7 ºC. Coletaram-se amostras de ovos em intervalos de 10 min, durante as primeiras três horas pós-fertilização (PF) e, posteriormente, em intervalos de 30min até a eclosão das larvas, para observação em estereomicroscópio equipado com câmera CMOS digital colorida, 10.0 MP e software para captura e análise de imagens (ISCapture). O efeito da densidade de estocagem de larvas do L. agassizii foi avaliado ao longo do 4º e 14º dias após a eclosão (DAE). Foram utilizadas 3600 larvas no 4º DAE, encontrando-se estas com o saco vitelínico totalmente absorvido, boca aberta e mantidas em jejum. As larvas foram submetidas às densidades de 5 (D5), 15 (D15) e 25 (D25) larvas.L-1, em caixas de polietileno (0,63 x 0,45 x 0,32 m), com 20 L de água. Utilizou-se um delineamento inteiramente casualizado com quatro repetições. As larvas foram alimentadas seis vezes ao dia, sendo cada refeição composta por náuplios de Artemia, na proporção 50 náuplios.larva-1 (4º ao 6º DAE), 100 (7º ao 9º DAE), 200 (10° ao 11º DAE) e 400 (12º ao 13º DAE) e por ração...
Keywords: Peixe; Peixe - Larva; Laboratorios; Hormonios; Embrião; Larvae